Phylogenetic Relatedness of Several Agarwood-Producing Taxa (Thymelaeaceae) from Indonesia - Shiou Yih Lee; Maman Turjaman; Rozi Mohamed (Tropical Life Sciences Research, 2018)
Indonesia is home to several tree taxa that are harvested for agarwood. This highly valuable oleoresin ironically was the cause for some species to become vulnerable due to gluttonous human activity. However, information on the genetic diversity of these endangered trees is limited. In this study, 28 specimens representing eight species from two genera, Aquilaria and Gyrinops, were collected from ex-situ and in-situ populations in Indonesia. Phylogenetic analysis conducted on DNA sequences of the nuclear ribosomal internal transcribed spacer (ITS) and the trnL-trnF intergenic spacer regions, revealed that Aquilaria and Gyrinops are paraphyletic when Aquilaria cumingiana is excluded. The phylogenetic analysis for ITS and trnL-trnF showed capability to categorise agarwoodproducing species based on their regions: East Indonesia and West Indonesia, using Wallace’s Line as the divider. In addition, we discuss challenges in species identification and taxonomy of agarwood-producing genera, and their conservation efforts in Indonesia. Indonesia merupakan tempat kediaman kepada beberapa taksa pokok yang dituai untuk kayu gaharu. Oleoresin yang sangat berharga ini secara ironinya telah menyebabkan beberapa spesies pokok penghasil gaharu terancam akibat ketamakan dan kerakusan manusia. Walau bagaimanapun, maklumat mengenai kepelbagaian genetik pokok-pokok terancam ini amatlah terhad. Dalam kajian ini, sebanyak 28 spesimen yang mewakili lapan spesies dari dua genera iaitu Aquilaria dan Gyrinops telah dikumpulkan dari populasi ex-situ dan in-situ di Indonesia. Analisis filogenetik yang dijalankan pada jujukan rantau penjarak transkripsi dalaman (ITS) ribosom nuklear dan rantau penjarak intergenik trnL-trnF telah menunjukkan bahawa Aquilaria dan Gyrinops adalah parafiletik apabila Aquilaria cumingiana dikecualikan. Analisis filogenetik untuk ITS dan trnL-trnF juga menunjukkan keupayaan untuk mengkategorikan spesies pokok penghasil gaharu berdasarkan kawasan masing-masing: Indonesia Timur dan Indonesia Barat, dengan menggunakan Garisan Wallace sebagai garisan pembahagi. Tambahan, kami juga turut membincangkan cabaran dalam pengenalpastian spesies dan taksonomi genera penghasil gaharu serta usaha dalam pemuliharaannya di Indonesia.